2021
DOI: 10.3280/pds2021-003015
|View full text |Cite
|
Sign up to set email alerts
|

L'efficacia del counseling universitario durante la pandemia da Covid-19. Un'indagine pilota sul benessere degli studenti

Abstract: La pandemia da Covid-19 e le conseguenti misure di confinamento hanno avuto un impatto globale sul benessere individuale, soprattutto su quello relativo agli studenti universitari. Il presente studio ha indagato in che misura un intervento di counseling eseguito durante la prima fase della pandemia da Covid-19 (marzo-ottobre 2020) era associato a variazioni significative nelle misure self report di Benessere Psicologico Generale, Regolazione Emotiva e Autoefficacia Percepita, in un gruppo di 49 studenti (37 f)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…In particular, being part of both the male group of students and the University of Foggia predicted a higher self-reported level of general health. The higher level of health declared by males is in line with the results of previous works, which demonstrated that male students tend to report a lower level of distress, and supports those studies that showed that female students are exposed to a greater risk of developing negative health consequences [ 19 , 30 ] and derive higher benefits from university counselling interventions than males [ 52 ]. General health was also significantly predicted by the university’s policy toward digital education.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, being part of both the male group of students and the University of Foggia predicted a higher self-reported level of general health. The higher level of health declared by males is in line with the results of previous works, which demonstrated that male students tend to report a lower level of distress, and supports those studies that showed that female students are exposed to a greater risk of developing negative health consequences [ 19 , 30 ] and derive higher benefits from university counselling interventions than males [ 52 ]. General health was also significantly predicted by the university’s policy toward digital education.…”
Section: Discussionsupporting
confidence: 90%